"Try again. Fail again. Fail better." - Poteko, Kaja (Teorija in praksa, 2014)
The article presents an analysis of the relationship between violence as depicted and performed in video games and its often-suggested prolongation into the physical world. The first part of the article gives a critique of the causal relation between the two types of violence through a theoretical reflection of the relationship between discourse and violence. The mentioned causality is problematized further through the distinction between the concepts of representation and performativity. The second and final part of the text moves to explain the pleasure of playing violent video games: it employs the psychoanalytical concept of death drive and connects it with the enjoyment in playing.
Keywords: death drive; discourse; diskurz; fantasy; fantazma; nagon smrti; nasilje; performativity; performativnost; video games; videoigre; violence